Perencanaan Strategis dan Pemodelan Obyek dalam Mengembangkan Sistem Chatbot - Kusumawati, Arie; Susanty, Yunisa (LPPM Universitas Islam 45 Bekasi, 2019)
Abstract Information technology and the Internet (Internet of Things) today have been implemented in all aspects of life. This seems to be in line with the growing public interest in e-commerce. The e-commerce growth can be used as a competitive advantage of an organization. The company currently has a chatbot product which is a combination of chat and e-commerce in one application. Chatbot is a computer application which is designed to understand text and audio that can interact with humans. XYZ company currently requires business strategy planning to gain a broader market share of their products. In addition, the latest chatbot design can attract customers’ interest in chatbots use of XYZ company. The analysis was carried out by using Strength, Weakness, Opportunity, and Treats (SWOT) analysis and Unified Modeling Language (UML) to analyze and design the new chatbot. The results obtained a new proposed business processes and analysis as well as new chatbot system design of XYZ company. Keywords: chatbot, business process, SWOT, UML, Fishbone Abstrak Teknologi informasi dan internet dewasa telah ini dimanfaatkan diseluruh aspek kehidupan. Hal ini nampaknya sejalan dengan bertumbuhnya minat masyarakat terhadap e-commerce. Pertumbuhan e-commerce yang terus mengalami peningkatan, dapat dijadikan suatu peluang yang telah dilihat oleh PT. XYZ. Saat ini perusahaan memiliki produk chatbot yang merupakan gabungan antara chat dan e-commerce dalam satu aplikasi. Chatbot adalah komputer yang telah dirancang khusus untuk memahami teks maupun audio dan dapat berinteraksi dengan manusia. PT XYZ saat ini membutuhkan perencanaan strategi bisnis yang dapat dipergunakan untuk mendapatkan pangsa pasar yang luas terhadap produk mereka dan juga perancangan chatbot yang terbaru sehingga pelanggan tertarik menggunakan chatbot dari PT XYZ. Analisis dilakukan dengan memanfaatkan SWOT analsisi dan UML untuk menganalisis serta perancangan chatbot terbaru. Hasil yang didapatkan adalah proses bisnis dan analisis serta perancanggan sistem chatbot terbaru PT.XYZ. Kata kunci: chatbot, proses bisnis, SWOT, UML, Fishbone